Theorising Hip-hop Dance In The Philippines: Blurring The Lines Of Genre, Mode And Dimension - Perillo, J. Lorenzo (Penerbit Universiti Sains Malaysia (USM Press), 2013)
While Hip-hop is recognised as a global musical culture, few studies have examined its practices of choreography. This essay privileges the ways Hiphop dancers in Manila theorise their practices through four main aspects— genre, mode, dimension and conflict—in order to draw attention to the principles of meaning-making in contemporary Hip-hop performance. This article suggests that a dance-based system of knowledge is helpful to our understanding of music and performance in Asia and the Pacific because it fleshes out internal discourses of Hip-hop and promotes a mindfulness regarding assumptions around the performing body.